PEMBENTUKAN KAWASAN TANPA ROKOK: ANALISA TERHADAP HAK AZASI MANUSIA DAN EFEKTIVITAS PERATURAN DAERAH - Rambe, Toguan; Mayasari, Seva (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
This article wants to look in depth at Deli Serdang Regency's policy of establishing smoking-free areas. This policy is contained in Deli Serdang Regency Regulation No. 2 of 2021 concerning non-smoking areas. The urgency of establishing this regulation is to discipline the public so that they do not smoke in random places, for example in health facilities or offices. The problems that will be studied include the extent to which it is effective in curbing the smoking habit and how acceptable it is to society because quite a few people say that smoking behavior is part of their lifestyle. The form of research is field research or field research, namely authentic data collection activities directly to the research location to see the object to be studied. In data collection techniques, researchers use observation and interviews, both methods will be straightforward in terms of extracting information. The results of this research show that the implementation and implementation of the Deli Serdang district regulations still finds several problem points and challenges, these problem points include: (1). Socialization that is not continuous, (2). Disobedient community attitude, (3). Insufficient facilities, (4). Sanctions that are not burdensome. The Deli Serdang Regency Government has made enforcement efforts, both repressive and preventive, for the community. These activities include providing education regarding the dangers posed by cigarette smoke and most importantly for the smooth running of government services by not spreading cigarette smoke to others. Apart from that, the government has also carried out monitoring and evaluation of people who violate it. Even though the overall implementation of these regulations has not been optimal, this is due to the absence of sanctions that have a deterrent effect on anyone who violates the regulations, so each of them needs strengthening.